واقع التخطيط الإستراتيجي ومعايير الجودة الشاملة من وجهة نظر أعضاء هيئة التدريس: دراسة حالة جامعة النيل الأبيض في الفترة (2020-2021م) - د . محمد الامين محمد يوسف كبر; د. أسامة حسين محمد يوسف كبر (White Nile Journal for Studies and Research, 2021)
The research aims at identifying the present reality of strategic planning in White Nile university on the light of inclusive quality based on the members of staff points of view. The two researchers have used the descriptive approach - survey method and SPSS program. The intended sample was the university staff members who spent more than three years in university service The main results are the White Nile university commitment to strategic planning in accordance with inclusive quality standards in fields of learning activities scientific research ,administrative affairs, social service and university values. The main recommendations are the university should coordinate with other scientific corporations to make joint- research, The strategy should pay more attention to the scientific environment, encourage creative deeds and give rewards to new ideas.